Cross-sectional Survey and Retrospective Analysis of a Large Cohort of Adults With Type 1 Diabetes With Long-Term Continuous Subcutaneous Insulin Infusion Treatment. (September 2014) - Joubert, Michael; Morera, Julia; Vicente, Angel; Rod, Anne; Parienti, Jean-Jacques; Reznik, Yves
Background. Continuous subcutaneous insulin infusion (CSII) is an established modality for intensive insulin treatment of type 1 diabetes (T1D), but long-term data concerning satisfaction, CSII function use, safety, and efficacy in real-life conditions are scarce. Methods. We analyzed a cohort of adult patients with T1D treated with CSII for more than 1 year in a single diabetes center. We performed a cross-sectional survey in 2010 (tolerance/satisfaction and behavior forms) and a retrospective analysis of medical records (including HbA1c level, hospitalization, and catheter infections). The primary objective was to assess long-term tolerance/satisfaction, and secondary objectives were safety and efficacy. Results. There were 295 patients analyzed. After a median duration of CSII use of 5 years, overall satisfaction was high for about 90% of patients. Mean CSII-related discomfort scores were low for work, recreation, and sleep and moderate for sport and sexual activity (2.5 ± 1.9, 2.6 ± 1.8, 2.6 ± 2.1, 3.4 ± 2.3, and 4.0 ± 2.9 of 10, respectively). Despite a high level of diabetes education, only one third of patients were using advanced CSII functions. During long-term follow-up, the safety of CSII treatment was good; the hospitalization rate was 0.18 patients/year, and catheter infections were scarce. The HbA1c level dropped about −0.5% independently from CSII duration ( P < .05). Conclusions. In this adult cohort, satisfaction and tolerance, together with safety, of CSII were maintained at long-term follow up. The sole basic functions of CSII were currently used by patients. A 0.5% decrease in the HbA1c level was maintained during the study period.